2022
DOI: 10.21123/bsj.2022.19.2.0409
|View full text |Cite
|
Sign up to set email alerts
|

Improved Firefly Algorithm with Variable Neighborhood Search for Data Clustering

Abstract: Among the metaheuristic algorithms, population-based algorithms are an explorative search algorithm superior to the local search algorithm in terms of exploring the search space to find globally optimal solutions. However, the primary downside of such algorithms is their low exploitative capability, which prevents the expansion of the search space neighborhood for more optimal solutions. The firefly algorithm (FA) is a population-based algorithm that has been widely used in clustering problems. However, FA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Iterated local search and guided local search algorithms belong to the former class, whereas evolutionary computation, particle swarm optimization, grey wolf optimization and ant colony optimization belong to the later one [15], [16]. Populationbased techniques are divided into two types, i.e., swarm intelligence algorithms and evolutionary algorithms [17], [18], on the basis of natural events that the algorithms represent. The theory of evolution is used by evolutionary algorithms to generate new species [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Iterated local search and guided local search algorithms belong to the former class, whereas evolutionary computation, particle swarm optimization, grey wolf optimization and ant colony optimization belong to the later one [15], [16]. Populationbased techniques are divided into two types, i.e., swarm intelligence algorithms and evolutionary algorithms [17], [18], on the basis of natural events that the algorithms represent. The theory of evolution is used by evolutionary algorithms to generate new species [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…of apparatuses with processing time can operate a job operation not similar in JSSP where each process must be performed by a particular apparatus; this is why when JSSP is compared with FJSSP, it is concluded that the FJSSP is more awkward due to its uncertainty when choosing the right apparatus out of a specific set of apparatuses that would handle each process of a task 5 .Two sub-problems were decomposed from the problem of scheduling jobs in FJSP that are routing and scheduling. A routing subproblem means each operation is assigned to a particular machine (out of a set of capable machines) and a scheduling sub-problem means that each assigned operation is given a sequence number for all selected machines in order to achieve optimized objectives from the feasible schedule 6,7 . In this research the makespan is decreased i.e., the highest time to complete the tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the proposed algorithm outperform GA and FIFO algorithms. In [14] the authors combined the FFA with VNS for Data Clustering (FA-VNS), the results showed that the proposed algorithm performance better than other well-known clustering algorithms in literature. In [15] the authors propose a modified FFA to effectively observe the network by introducing a new health function for early detection of suspicious nodes, the results showed that the proposed algorithm reduces the number of suspicious nodes.…”
Section: Introductionmentioning
confidence: 99%